2017
DOI: 10.1007/s00404-017-4457-y
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal serum homocysteine and uterine artery Doppler as predictors of preeclampsia and poor placentation

Abstract: NCT02854501.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…Higher maternal plasma homocysteine concentrations in preeclamptic pregnancies as compared to normotensive were widely reported [93,125,130,132,133,134,135,136,137]. Overall, these differences seem to be present at all of the investigated time points across the gestation, starting from early pregnancy before 20 weeks [138,139,140,141,142] and in both severe and non-severe forms of PE. Comprehensively, this finding led to a conclusion that high homocysteine in early pregnancy constitutes a risk factor for PE.…”
Section: No Adma and Homocysteine In Preeclampsiamentioning
confidence: 86%
See 1 more Smart Citation
“…Higher maternal plasma homocysteine concentrations in preeclamptic pregnancies as compared to normotensive were widely reported [93,125,130,132,133,134,135,136,137]. Overall, these differences seem to be present at all of the investigated time points across the gestation, starting from early pregnancy before 20 weeks [138,139,140,141,142] and in both severe and non-severe forms of PE. Comprehensively, this finding led to a conclusion that high homocysteine in early pregnancy constitutes a risk factor for PE.…”
Section: No Adma and Homocysteine In Preeclampsiamentioning
confidence: 86%
“…Comprehensively, this finding led to a conclusion that high homocysteine in early pregnancy constitutes a risk factor for PE. Therefore, attempts to introduce Hcy measurement into a screening test for PE to improve the prediction model, for example, by combining it with uterine artery Doppler test in the second trimester, resulted in being valuable [140]. However, there are also studies that rejected an association between elevated Hcy in early second trimester and subsequent PE [143,144,145].…”
Section: No Adma and Homocysteine In Preeclampsiamentioning
confidence: 99%
“…Studies have reported inconsistent associations between maternal homocysteine, measured at different time points in pregnancy and placenta-mediated complications [10, 11]; even among larger cohort and case-control studies measuring homocysteine from early pregnancy, the associations are inconsistent [1218]. The discrepancies could be due to moderating factors like high-risk pregnancy and differences in population frequencies of the MTHFR 677C>T polymorphism that can lead to moderately elevated homocysteine [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 Among numerous pathological changes involved in preeclampsia, the most important are endothelial dysfunction, local inflammation, and oxidative stress. 29 – 31 Previous studies have shown that increased Hcy levels augment cellular oxidative stress and cause generalized endothelial dysfunction, 32 – 34 and increased plasma oxidative stress has been reported in mothers with preeclampsia. 35 In addition, elevated Hcy levels appear to impair endothelium and lead to ischemic hypoxia through impaired nitric oxide-dependent vasodilation, endothelial toxicity and injury, oxidative stress, and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%